Does diversity in team members’ agreeableness benefit creative teams? - LEE, Sean T. H. (Institutional Knowledge at Singapore Management University, 2020)
Although deep-level diversity among team members are often discussed as important catalysts of team creativity, little is currently understood about the impact of diversity in team members’ personality on team creativity and team satisfaction. We propose that diversity in team members’ agreeableness would reduce the effectiveness of creative teams through its impact on team conflict experienced. To test our hypotheses, we recruited 93 student teams to participate in a laboratory study where each member had their personality traits assessed before engaging in a team creativity task. We found that diversity in team members’ agreeableness was positively associated with team task conflict experienced which, in turn, was negatively associated with team creativity. Additionally, we found that diversity in team members’ agreeableness was positively associated with team relationship conflict, which, in turn, was negatively associated with team satisfaction. Implications and future directions are discussed.